Production of Butylamine in the Gas Phase Hydrogenation of Butyronitrile over Pd/SiO2 and Ba-Pd/SiO2. (3rd July 2015) - Hao, Y.; Li, M.; Cárdenas-Lizana, F.; Keane, M. A.
Abstract: The gas phase (1 atm, 473-563 K) hydrogenation of butyronitrile has been studied over Pd/SiO2 and Ba-Pd/SiO2 . Catalysts characterisation involved TPR, H2 /NH3 chemisorption/TPD, XRD and TEM measurements. The incorporation of Ba with Pd resulted in the formation of smaller metal nano-particles (7 nm vs. 28 nm) with a resultant (seven-fold) higher H2 chemisorption and decreased total surface acidity (from NH3 chemisorption/TPD). Temperature related activity maxima were observed for both catalysts and are associated with thermal desorption of the nitrile reactant. Exclusivity to the target butylamine was achieved at T ≥ 543 K where Ba-Pd/SiO2 delivered higher selective hydrogenation rate(91 mol h −1 mol Pd -1 ) than Pd/SiO2 (54 mol h −1 mol Pd −1 ), attributed to greater availability of surface reactive hydrogen. Lower surface acidity served to minimise condensation to higher amines. The rate and selectivity to butylamine exceed those previously reported for gas phase operation. Abstract :